Url-based Classification Features In Preventing Ransomware Cyber-attacks - Nurlida Basir; Melad Mohamed Al-Daeef; Nurzi Juana Mohd Zaizi; Nur Fatin Nabila Mohd Rafei Heng; Melinda Melinda (Semarak Ilmu Publishing, 2024)
Indexed by MyCite